Clinical Relevance of Cardiac Troponin Assessment in Patients Undergoing Carotid Endarterectomy. Issue 4 (April 2016) - Grobben, R.B.; Vrijenhoek, J.E.P.; Nathoe, H.M.; Den Ruijter, H.M.; van Waes, J.A.R.; Peelen, L.M.; van Klei, W.A.; de Borst, G.J.
Abstract : Objective: Myocardial infarction (MI) is a frequent complication of carotid endarterectomy (CEA), yet most events are silent. Routine post-operative monitoring of cardiac troponin was implemented to facilitate timely recognition of MI and stratify high risk patients. The aim was to evaluate the incidence of troponin elevation after CEA and its association with adverse cardiovascular events. Methods: This analysis included patients ≥60 years old who underwent CEA, whose troponin-I levels were routinely monitored post-operatively and were included in a cohort study that assessed clinical outcomes. A clinical troponin cutoff of 60 ng/L was used. The primary endpoint was the composite of MI, stroke, and cardiovascular death. Secondary endpoints were MI, stroke, coronary intervention, cardiovascular death, and all cause death. Results: 225 consecutive patients were included in the analysis. Troponin elevation occurred in 34 patients (15%) and a post-operative MI was diagnosed in eight patients. After a median follow up of 1.8 years (IQR 1.0–2.6), the primary endpoint occurred in 29% of patients with troponin elevation versus 6.3% without (HR 5.6, 95% CI 2.4–13), MI in 24% versus 1.6% (HR 18.0, 95% CI 4.7–68), stroke in 5.9% versus 4.2% (HR 1.4, 95% CI 0.3–6.7), coronary intervention in 5.9% versus 2.6% (HR 2.7, 95% CI 0.5–14), cardiovascular death in 5.9% versus 0.5% (HR 11.8, 95% CI 1.1–131), and all cause death in 15% versus 5.8% (HR 3.0, 95% CI 1.0–8.7), respectively. Incidences of the primary endpoint and all cause mortality in patients with a post-operative MI versus "troponin only" were 25% versus 7.7% and 25% versus 12%, respectively. Conclusion: Troponin elevation after CEA occurred in 15% of patients. The incidence of adverse cardiovascular events was significantly higher in patients with troponin elevation, which was mainly attributable to silent non-ST segment elevation MIs that occurred in the early post-operative phase.